Elbow Injuries Among MLB Pitchers Increased During Covid-19 Disrupted Season, But Not Other Baseball Injuries - Chelsea Martin; Jozef Palasiewicz; Jesse Grullon; Ellen Shanley; Charles Thigpen; Daniel Kline; Stefan Kluzek; Gary Collins; Garrett Bullock (International Journal of Sports Physical Therapy)
# Background